Laduni Science On Muhammad Luthfi Ghozali’s Perspective - Fatoni, Muhamad; Naim, Ngainun (UIN Sayyid Ali Rahmatullah Tulungagung, 2020)
Abstract This article examines the science of laduni and how to acquire it. Laduni science is generally perceived as a supernatural science that cannot be obtained aside from by few individuals. This knowledge is often associated with things that happen abruptly without any preceding process. Muhammad Lutfi Ghozali disproved this assumption by proposing logical, rational arguments and sticking to the naṣ of the Qur'an and Hadith. Muhammad Luthfi Ghozali explained that laduni science has an analytical mechanism. Those who understand the substance of laduni science and construct causal mechanisms will be achievable to acquire this knowledge. The thought of Muhammad Lutfi Ghozali places a comprehension of laduni science that seems mystical and irrational. Keywords: laduni science, Muhammad Luthfi Ghozali, rational, mystical Abstrak Artikel ini membahas tentang ilmu laduni dan cara-cara mendapatkannya. Ilmu laduni umumnya dipahami sebagai ilmu mistik yang tidak mungkin diperoleh kecuali oleh sebagian kecil orang. Ilmu ini kerapkali dihubungkan dengan hal yang terjadi secara tiba-tiba tanpa adanya proses yang mendahuluinya. Muhammad Luthfi Ghozali membantah anggapan tersebut dengan mengajukan argumentasi logis, rasional serta tetap berpegang pada naṣ Al-Qur’an dan hadits. Muhammad Luthfi Ghozali menjelaskan bahwa ilmu laduni memiliki mekanisme rasional. Mereka yang memahami substansi ilmu laduni dan membangun mekanisme sebab akan mungkin untuk mendapatkan ilmu ini. Pemikiran Muhammad Luthfi Ghozali ini mendudukkan pemahaman tentang ilmu laduni yang seolah mistik dan tidak rasional. Kata kunci: ilmu laduni, Muhammad Luthfi Ghozali, rasional, mistik.